Phosphate and borophosphate glasses modified with transition metal oxides - Hostinský, Tomáš (Univerzita Pardubice, 2025)
This dissertation investigates the structure and properties of newly developed phosphate and borophosphate glasses modified with transition metal oxides (Nb2O5, WO3, MoO3) and containing various alkali and transition metal oxides (Li2O, Na2O, Ag2O). Several compositional series were prepared and systematically studied in terms of physicochemical, thermal, electrical, and structural properties. The results show that niobium oxide significantly strengthens the glass network and improves chemical and thermal stability. The addition of B2O3 led to the formation of mixed borophosphate glasses, studied via 11B and 31P MAS NMR and Raman spectroscopy. In silvercontaining borophosphate glasses with WO3 and MoO3, a positive mixed glass former effect (MGFE) was observed, with the highest conductivity achieved in a phase-separated sample. In lithium–tungsten borophosphate systems, the glass structure was successfully optimised to enhance conductivity without compromising phase homogeneity. The maximum DC conductivity reached 1.58·10−6 Ω−1·cm−1 at 30 °C. The findings contribute to a deeper understanding of structure–property relationships in phosphate glasses and demonstrate their potential as tunable solid electrolytes for energyrelated applications.
Fosfátová a borofosfátová skla modifikovaná oxidy přechodných kovů
Keywords: fosfátová skla; borofosfátová skla; termická analýza; struktura skel; NMR spektroskopie; Ramanova spektroskopie; Phosphate glasses; Borophosphate glasses; Thermal analysis; Glass structure; NMR spectroscopy; Raman spectroscopy